Multimodalidade e produção de sentidos em narrativas orais infantis - Falcão, Rosineide Costa (2015)
The Multimodality in oral narratives is the subject of this research study, being relevant in the sense that multimodal resources are conducive production senses infant oral narratives. Thus, this work proposes investigating multimodal features that favor the production of meaning in children's oral narratives. We base our research in the context of multimodal functioning of language, backed by McNeill (2000), Kendon (1982, 2000), Cavalcante (1999, 2009), Fountain (2011) and Fountain et al (2014), and in studies of oral narratives and children's literature, with contributions from Marcuschi (2003), Bettelheim (1979), Matos (2009), Franz (1981), Sisto (2012), Abramovich (2000), Gillig (1999). The methodology was qualitative, observational nature - the type case study. To collect data, seven children attended a school municipal school system of Recife, enrolled in the second grade of elementary school. A classic tale adapted from children's literature and a unique tale were recorded in audio and subsequently presented to children at two different times. After heard the tales for the second time, children recounted each. The retellings were filmed to be transcribed through the ELAN software (Eudico Linguistic Annotator), which enables simultaneous record speech and gestures. Selected as an analysis category the verbal and gestural plan plan, comprising the multimodal envelope, adopted by Ávila Nobrega (2010) and Source (2011). We know that the child's first contact with the text is: speaking, hearing, feeling and seeing with the eyes of imagination. With data analysis, we conclude that the narratives of the stories there was a prevalence of verbal production associated with gesticulations. But in classic tale, we see greater variety of gestures and details in the narrative because of sedimentation of multimodal resources at the known history. In the contemporary tale, we find limitations of the information in the narratives and greater scarcity sign, perhaps not known by children.